Near infra-red light responsive carbon nanotubes@mesoporous silica for photothermia and drug delivery to cancer cells. (September 2020) - Li, B.; Harlepp, S.; Gensbittel, V.; Wells, C.J.R.; Bringel, O.; Goetz, J.G.; Begin-Colin, S.; Tasso, M.; Begin, D.; Mertz, D.
Abstract: Among smart activable nanomaterials used for nanomedicine applications, carbon-based nanocomposites are well known to ensure phototherapy while their use for controlled drug delivery is still rarely investigated. In this work, original hybrid mesoporous silica (MS)–coated carbon nanotubes (CNTs) nanoplatforms have been designed to provide phototherapy combined with drug release mediated by NIR laser excitation. The responsive CNT@MS are chemically modified with original isobutyramide (IBAM) grafts acting as non-covalent binders, which ensure a very high drug loading capacity (≥to 80 wt%) of the antitumor drug doxorubicin (DOX) as well as the final adsorption of a human serum albumin (HSA) shell as biocompatible interface and drug gate-keeping. The drug is demonstrated to unbind from the nanocomposite only upon photothermal excitation and to release in the solution. Such smart platforms are further shown to deliver drug upon several pulsatile NIR excitations with controlled temperature profiles. Regarding antitumor action, we demonstrate here that the NIR light induced photothermic effect from the nanocomposites is the main effect accounting for cancer cell toxicity and that DOX delivery mediated by the NIR light brings an additional toxicity allowing a synergistic effect to efficiently kill tumor cells. Finally, when our nanocomposites are embedded within a hydrogel mimicking extracellular matrix, the resulting smart responsive scaffolds efficiently release DOX upon NIR light to the cells localized above the composite hydrogel. These results demonstrate that such nanocomposites are highly promising as new components of implantable antitumor scaffolds that are able to respond to external stimuli in time and location for a better disease management. Graphical abstract: Image 1 Highlights: Hybrid carbon nanotubes@mesoporous silica are designed. Isobutyramide grafts ensure a very high drug loading capacity (≥to 80 wt%). They provide NIR-mediated phototherapy combined with pulsatile drug release. Upon NIR light applied, they induce cancer cell toxicity. Such nanocomposites are embedded within a hydrogel mimicking extracellular matrix.